Mechanisms of hyperinsulinaemia in Child's disease grade B liver cirrhosis investigated in free living conditions. (1st December 2002) - Greco, A V; Mingrone, G; Mari, A; Capristo, E; Manco, M; Gasbarrini, G
Abstract : Aims: Human liver cirrhosis is commonly associated with increased fasting and glucose induced insulin concentrations. However, whether the hyperinsulinaemia is a consequence of increased pancreatic insulin secretion, decreased hepatic insulin removal, or impaired feedback regulation of insulin secretion is still doubtful. To investigate these issues, insulin secretion—during 24 hours of standardised living conditions—insulin sensitivity, and hepatic insulin extraction were assessed in cirrhotic patients compared with matched healthy subjects. Patients: Nine Child's disease grade B cirrhotic patients and seven healthy volunteers, participated in the study. The subjects were studied on two separate days, one for the assessment of insulin secretion during a standardised 24 hour life period (calorimetric chamber), and one for the determination of insulin sensitivity. Methods: Insulin secretion rates were reconstructed from plasma C peptide concentrations by deconvolution, and indices of β cell function were derived using a mathematical model describing the functional dependence of insulin secretion on plasma glucose concentrations. Insulin sensitivity was determined using the euglycaemic hyperinsulinaemic clamp technique. Results: Cirrhotic patients showed a marked hypersecretory response, both in absolute terms (mean (SEM) 295 (53) versus 138 (11) nmol/m 2, p<0.02), and in relation to glucose (175 (26) versus 57 (5) pmol/min/m 2, p<0.02). In particular, the β cell dose-response function was shifted upward compared with controls. The sensitivity of insulin secretion to the rate of glucose change was also increased. Insulin sensitivity, markedly reduced in cirrhosis (157 (10) versus 296 (30) ml/min/m 2, p<0.002), was strongly inversely correlated ( r =0.89, p<0.002) in these patients with insulin secretion at 5 mM glucose. Insulin clearance and hepatic insulin extraction were not reduced. A frank hypermetabolism with increased lipid oxidation was found in this series. Conclusions: This study suggests that hyperinsulinaemia, at least in Child's disease grade B cirrhotic patients, is the consequence of increased β cell sensitivity to glucose, while hepatic insulin extraction does not seem to play a significant part.